Pengaruh Pengetahuan Investasi, Risk Tolerance, Dan Self Efficacy Terhadap Intensi Investasi Pasar Modal Pada Generasi-Z - Reza Fitriana Rizkia; Fitria Ardia Pramesti; Siti Amaroh (ISLAMIC BUSINESS and FINANCE, 2023)
Investments in the country's actual economy and its capital market will increase as a result of globalization. Because of this, the capital market requires members of Generation Z to have a high level of self-awareness. The purpose of this study is to examine how generation Z investors' levels of investing expertise, risk aversion, and confidence influence financial market performance. The goal of this research was to identify the factors (investment knowledge, risk tolerance, and self-efficacy) that influence people's decisions to put money into the stock market. Gen Z is the focus of this investigation. Non-probability type purposive sampling was used to choose the 200 respondents who would make up this study's sample of members of Generation Z. The validity and reliability tests were used to evaluate the research instrument, and the classical assumption test and multiple regression analysis were used to analyze the collected data. Capital market investing intentions are positively related to investment knowledge, risk tolerance, and confidence, according to the investigation. The findings of this study have important implications for encouraging younger generations' interest, trust, and self-awareness in the capital market.Keywords: Investment Intensity, Investment Knowledge, Risk Tolerance, Self Efficacy.